Social Media and E-commerce as Mechanisms to Enhance Entrepreneurship Among Graduate Students - Betancourt, Ignacio Ortiz; Téllez, María del Carmen Meza (European Journal of Economics and Business Studies, 2019)
In recent years, entrepreneurship has been one of the most discussed issues among government agencies, education institutions and international organizations, given the restrictions on the labor market. The above, since entrepreneurship is considered as an important mechanism to generate direct and indirect jobs. However, the increasing participation of electronic mechanisms in society has transformed the way we carry out our activities, redefining the processes through which the various goods and services are produced and offered. Therefore, there is a consensus towards the need for entrepreneurs to adopt a profile oriented towards social media and electronic commerce. However, this topic is still in its first stages, so it is necessary to identify how much these concepts have been integrated into the university entrepreneurial ecosystem, which represents one of the main channels for promoting entrepreneurial culture. After a study among a group of students graduated from university, it was detected that they attach high importance to social networks and electronic commerce, since they allow them to increase their presence in the markets at a relatively low cost; however, its adoption process has been heterogeneous, given the lack of knowledge of many tools and the lack of financing. Finally, a series of recommendations that could improve these skills among future entrepreneurs from the university level are indicated.
Keywords: entrepreneurial culture, digital skills, self-employment.